Peran Pemerintah dalam Mengoptimalkan Dinamika Wirausaha: Mendukung Kemajuan Ekonomi Indonesia Khususnya Wilayah Jakarta - Ciek Julyati Hisyam; Kailla Putri Aisyah; Siti Umi Khoiriah; Syafaa Marwah Augea (Universitas 45 Surabaya, 2024)
This research analyzes the dynamics of entrepreneurship in Jakarta using theoretical concepts from Pierre Bourdieu, especially the concepts of